Antimicrobial Activities of Actinobacteria Isolated from Marine and Terrestrial Samples in Lombok Island, Indonesia - Ratnakomala, Shanti; Krause, Janina; Sari, Miranti Nurindah; Kusumawardhani, Dinihari Indah; Kusmiati, Mia; Lisdiyanti, Puspita (BRIN, 2022)
During our study on exploring actinobacteria from Indonesian sources, we selected 59 strains of actinobacteria isolated with five different isolation methods from Lombok Island Indonesia. The aim of this research was to isolate and characterize those actinobacteria, and to screen the microbial activities against 5 bacterial tested. Six soil samples from Lombok Island were processed. Totally, 59 isolated were selected. Of these strains, 31 strains showed antibiotic activity. Seventeen strains from 59 strains have been identified by 16S rRNA gene sequencing, and most dominant of the strains belongs to the genus Streptomyces. Three of them were chosen for further experiments due to their broad activity against four of five test strains. From two strains, at least one bioactive substance could be extracted. As only few bioactive substances could be extracted with ethyl acetate from liquid cultures more experiments should be performed on this subject. More solvent extraction should be tested as well as other production media. In conclusion, present study did now reveal bioactive actinobacteria were isolated from soil samples in Lombok Island. Antimicrobial compound has also been detected which is active against a broad range of pathogens. These findings may have an importance to produce potentially new antibiotic substances from actinobacteria indigenous Indonesia.